Crystal structure of bis(μ-N-i-propyl-N-n-propyldithiocarbamato-κ2S:S′) bis(N-i-propyl-N-n-propyldithiocarbamato-κ2S,S′)dizinc(II), C28H56N4S8Zn2 - Tan, Yee Seng *; Tiekink, Edward R. T. * (De Gruyter Open Access, 2018)
C28H56N4S8Zn2, monoclinic, P21/n (no. 14), a=9.4123(2) Å, b=19.2708(4) Å, c=11.5228(3) Å, β=107.202(2)°, V= 1996.54(8) Å3, Z=2, Rgt(F)=0.0254, wRref(F2)=0.0572, T=100(2) K